Why Might Bacterial Pathogens Have Small Genomes?. (December 2017) - Weinert, Lucy A.; Welch, John J.
Abstract : Bacteria that cause serious disease often have smaller genomes, and fewer genes, than their nonpathogenic, or less pathogenic relatives. Here, we review evidence for the generality of this association, and summarise the various reasons why the association might hold. We focus on the population genetic processes that might lead to reductive genome evolution, and show how several of these could be connected to pathogenicity. We find some evidence for most of the processes having acted in bacterial pathogens, including several different modes of genome reduction acting in the same lineage. We argue that predictable processes of genome evolution might not reflect any common underlying process. Trends: Bacterial pathogens often have smaller genomes and fewer genes than their non- or less pathogenic relatives. The same pattern is seen within some bacterial species, with repeated transitions to higher virulence associated with reductive genome evolution. Several major questions about the pattern remain open, including its generality, and the causal relationships involved. Multiple population genetic processes have been invoked to explain reductive genome evolution, and several of these are plausibly associated with the evolution of pathogenicity.